Accelerated 129Xe MRI morphometry of terminal airspace enlargement: Feasibility in volunteers and those with alpha‐1 antitrypsin deficiency. Issue 1 (25th November 2019) - Ouriadov, Alexei; Guo, Fumin; McCormack, David G.; Parraga, Grace
Abstract : Purpose: Multi‐b diffusion‐weighted hyperpolarized inhaled‐gas MRI provides imaging biomarkers of terminal airspace enlargement including ADC and mean linear intercept (Lm ), but clinical translation has been limited because image acquisition requires relatively long or multiple breath‐holds that are not well‐tolerated by patients. Therefore, we aimed to accelerate single breath‐hold 3D multi‐b diffusion‐weighted 129 Xe MRI, using k‐space undersampling in imaging direction using a different undersampling pattern for different b‐values combined with the stretched exponential model to generate maps of ventilation, apparent transverse relaxation time constant ( T 2 ∗ ), ADC, and Lm values in a single, short breath‐hold; accelerated and non‐accelerated measurements were directly compared. Methods: We evaluated multi‐b (0, 12, 20, 30, and 45.5 s/cm 2 ) diffusion‐weighted 129 Xe T 2 ∗ /ADC/morphometry estimates using acceleration factor (AF = 1 and 7) and multi‐breath sampling in 3 volunteers (HV), and 6 participants with alpha‐1 antitrypsin deficiency (AATD). Results: For the HV subgroup, mean differences of 5%, 2%, and 8% were observed between fully sampled and undersampled k‐space for ADC, Lm, and T 2 ∗ values, respectively. For the AATD subgroup, mean differences were 9%, 6%, and 12% between fully sampled and undersampled k‐space for ADC, Lm and T 2 ∗ values, respectively. Although mean differences of 1% and 4.5% were observed between accelerated and multi‐breath sampled ADC and Lm values, respectively, mean ADC/Lm estimates were not significantly different from corresponding mean ADC M /Lm M or mean ADC A /Lm A estimates (all P > 0.60, A = undersampled and M = multi‐breath sampled). Conclusions: Accelerated multi‐b diffusion‐weighted 129 Xe MRI is feasible at AF = 7 for generating pulmonary ADC and Lm in AATD and normal lung.